The Influence of the Mallogo Traditional Game on the Social Skills of Children Aged 5-6 Years in Amalia II Kindergarten, South Labuhanbatu Regency, 2022/2023 Academic Year - Nur Paujiah Harahap; Anita Yus (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of the traditional mallogo game on the social skills of children aged 5-6 years at Amalia II Kindergarten, Labuhan Batu Selatan Regency, in the 2022/2023 academic year. This research uses a quasi-experimental design in the form of The Equivalent Time Sample Design. The research population was all children aged 5-6 years in Kindergarten Amalia II in 2 classes. The sampling technique uses simple random sampling technique so that the sample is the Ar-Rahim class, which consists of 30 children. The variables of this study consist of the independent variable, namely the traditional mallogo game and the dependent variable, namely social skills. Data collection techniques using observation with observation sheet instruments. Data were analyzed using the t-test with a significant level of α=0.05 with a critical value of 0.161. The results showed that there was a significant effect of the traditional mallogo game on the social skills of children aged 5-6 years at Kindergarten Amalia II, South Labuhan Batu Regency. This is evidenced by the results of statistical calculations of the difference in the average data given the second treatment with data without being given the second treatment, where the results of tcount (13.808) > ttable (1.699) which means that Ha is accepted and Ho is rejected or means that the traditional mallogo game has a significant effect on social skills of children aged 5-6 years in Kindergarten Amalia II Labuhan Batu Selatan District for the 2022/2023 Academic Year.